Lana–Match algorithm: a parallel version of the Rete–Match algorithm - Aref, Mostafa M; Tayyib, Mohammed A (Parallel computing, 1998)
The Rete–Match algorithm is a matching algorithm used to develop production systems. Although this algorithm is the fastest known algorithm, for many patterns and many objects matching, it still suffers from considerable amount of time needed due to the recursive nature of the problem. In this paper, a parallel version of the Rete–Match algorithm for distributed memory architecture is presented. Also, a theoretical analysis to its correctness and performance is discussed.